Clinical Effects and Safety of Deep Dry Needling for Upper Trapezius Myofascial Pain Syndrome: A Prospective Single-Group Study in Tripoli, Libya - Fatima Gazah (AlQalam Journal of Medical and Applied Sciences, 2026)
Myofascial pain syndrome (MPS) is a common musculoskeletal condition characterised by myofascial trigger points, pain, and functional limitations. Although dry needling is widely used in physiotherapy for myofascial pain, locally derived clinical evidence from Libya remains limited. This study evaluated the short-term clinical effects and safety of deep dry needling in patients with upper trapezius myofascial pain syndrome. A prospective, quasi-experimental, one-group pretest–posttest case series was conducted in the physiotherapy department of Al-Kahili Specialized Clinic, Tripoli, Libya. Ten patients (5 men and 5 women; mean age 37.2 ± 15.2 years) with chronic neck and shoulder pain and a clinically confirmed active upper trapezius myofascial trigger point were recruited. Participants received three weekly sessions using Hong's pistoning dry-needling technique. Pain intensity was assessed using the Visual Analogue Scale (VAS), local tenderness using a 4-point manual palpation scale, and neck-related disability using the Neck Disability Index (NDI). Assessments were performed at baseline (T0), immediately after the first treatment session (T1), and 4 weeks after the start of treatment (T2), with the NDI assessed at T0 and T2. Adverse events were recorded throughout the treatment period. Mean VAS pain scores decreased from 7.4 ± 1.2 at T0 to 6.0 ± 1.4 at T1 and 4.0 ± 1.8 at T2. The mean reduction from T0 to T2 was 3.4 ± 1.0 points (paired t(9) = 11.13, p < 0.001), and 9 of 10 participants (90%) achieved a ≥30% reduction in pain. Manual palpation tenderness decreased from 2.5 ± 0.5 at T0 to 1.1 ± 1.0 at T2 (paired t(9) = 6.33, p < 0.001). Mean NDI scores decreased from 23.8 ± 7.5 at T0 to 15.9 ± 7.7 at T2 (paired t(9) = 8.23, p < 0.001). No serious adverse events were reported. The observed adverse events included transient post-needling soreness (40%), superficial bruising (30%), minor capillary bleeding (30%), and transient dizziness (20%), all of which resolved without further intervention. These findings suggest that deep dry needling may be associated with short-term improvements in pain, local tenderness, and neck-related disability in patients with upper trapezius myofascial pain syndrome. However, the small sample size and absence of a control group limit the strength of the conclusions, and larger controlled studies are needed to confirm these findings.